2019
DOI: 10.1177/0300060519856750
|View full text |Cite
|
Sign up to set email alerts
|

Pre-cardiopulmonary bypass administration of dexmedetomidine decreases cardiac troponin I level following cardiac surgery with sevoflurane postconditioning

Abstract: Objective This study was performed to determine the effect of dexmedetomidine (DEX) administration on myocardial damage in cardiac surgery with sevoflurane postconditioning. Methods We retrospectively examined all cardiac valve replacement surgeries from 1 April 2016 to 30 April 2017. Eligible patients were divided into two groups based on whether DEX was infused. DEX infusion was permitted only between intubation and the beginning of cardiopulmonary bypass (CPB). Sevoflurane was inhaled via the standard postc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It has also been shown that TnT elevation in children reflects myocardial damage not only after the surgery, but also after chemotherapy with cardiotoxic doxorubicin [ 23 ]. The difficulty and complexity of performed surgery, cardiopulmonary bypass and cross-clamp times, surgical and reperfusion injury have all been found to cause major postoperative troponin release [ 19 , 24 , 25 ]. Troponin concentration has been found to predict myocardial complications such as arrhythmias, cardiogenic shock and in-hospital mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that TnT elevation in children reflects myocardial damage not only after the surgery, but also after chemotherapy with cardiotoxic doxorubicin [ 23 ]. The difficulty and complexity of performed surgery, cardiopulmonary bypass and cross-clamp times, surgical and reperfusion injury have all been found to cause major postoperative troponin release [ 19 , 24 , 25 ]. Troponin concentration has been found to predict myocardial complications such as arrhythmias, cardiogenic shock and in-hospital mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of literature describes troponin reference values and their role in outcome prognosis following cardiac surgery, both in adult and paediatric populations [4][5][6]19]. Some authors suggest that TnT concentration in children is a powerful marker of outcome after cardiac surgery [20,21].…”
mentioning
confidence: 99%
“…Referring to dexmedetomidine, a small prospective trial including 38 patients undergoing CABG surgery indicated that myocardial damage was not reduced by dexmedetomidine, although a higher cardiac index and lower mean pulmonary arterial pressures were observed in the dexmedetomidine treated group [ 101 ]. In a retrospective analysis, Zhou et al indicated that in patients undergoing valve surgery post-operative release of myocardial biomarkers (cardiac troponin I) was lower in patients receiving dexmedetomidine during the procedure [ 102 ], an observation that was confirmed in a small prospective randomized study in 28 patients undergoing valve replacement [ 103 ] and in patients undergoing CABG surgery [ 104 ]. However, large outcome trials are pending and the available data on clinically relevant cardioprotection by dexmedetomidine are of low to moderate quality.…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%
“…Patients with perioperative myocardial ischemia after cardiac surgery with or without cardiopulmonary bypass (CPB) results in cardiac arrhythmia and postoperative myocardial dysfunction [1]. Overall, cardiac arrhythmias were prevalent in 5.3% of the general population and are considered a vital source of mortality and morbidity in cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%